From Campus to Career: How Emerging Technology Influences Placement Outcomes ‎through The Student Preparedness and Confidence - B, Karthik; A S, Sathish (International Journal of Accounting and Economics Studies, 2025)
Purpose: The study aims to investigate how emerging technology is vital for gaining a ‎competitive advantage in student placement outcomes in the universities of Tamil Nadu. ‎Approach: The conceptual framework of the research is based on various technological factors ‎adapted from human capital theory and social cognitive theory, which contribute to the outcome. ‎The relationship examines the mediating effects of student preparedness and confidence within ‎the model. A sample of 402 students from different private universities in Tamil Nadu was ‎surveyed using a pretested questionnaire. The empirical validation of the framework and analysis ‎was done using smart PLS structural equation modelling. The research also investigates how age ‎and gender act as moderators to better understand the various impacts of technology-enhanced ‎learning.Result: Student preparedness strongly predicts student confidence, boosting placement success. ‎These findings offer theoretically and practically valuable insights that can guide university ‎administrators, policymakers, and corporate recruiters in enhancing graduate employability in an ‎increasingly digital educational landscape‎.
Keywords: Emerging Technology; Student Preparedness; Student Confidence; Placement Outcome; Higher ‎Education Employability